Bacteria associated with respiratory infections in poultry - Jesto George (Department of Veterinery Microbiology, College of Veterinary and Animal Science, 2007)
This study was undertaken to isolate and identify of bacteria from respiratory tract of poultry and to study the antibiogram of the isolates. Birds showing respiratory signs were sacrificed, postmortem examination was conducted and samples such as nasal, tracheal and air sac swabs and lungs were collected after taking all sterile precautions. A total of 105 samples were collected by sacrificing birds showing clinical signs. Isolation of causative bacteria was made by culturing on brain heart infusion agar, Mac Conkey agar and blood agar. For identification of isolates all the procedures were followed as described by Barrow and Feltham (1993). A total of 31 bacterial isolates were obtained from samples. A total of 12 Escherichia coli isolates were isolated and identified, 4 Pasteurella multocida isolates and 15 Staphylococcus sp. Isolates were isolated and identified biochemically. Out of 15 Staphylococcus sp. isolated and identified 11 isolates (73.33 per cent) were coagulase negative This result indicate that CoNS were more frequently isolated from staphylococcal infections although they do not possess the virulent coagulase activity. So importance must be given to CoNS also, as given to coagulase positive staphylococci and much study need to be diverted to find the virulence factors and role of them in producing bacterial infections in poultry. Multi drug resistance (resistance to at least three antimicrobials) was found among all E. coli isolates obtained in the study. Hence it may be concluded that the high level of resistance observed among poultry E coli isolates obtained in the study may be due to incorporation of antibiotics in feed as growth promoters. As 100 per cent sensitivity is shown to enrofloxacin and chloramphenicol by P. multocida isolates, these two drugs may be used for treating pasteurellois. Amoxycillin clavulanic acid (Ac) and cephalexin (Cp) was found to be the most effective antibiotic against Staphylococcus sp. in the study. The plasmid DNA content of the seven isolates of E. coli was analysed on agarose gel electrophoresis but correlation between the number of plasmids and antibiotic resistance could not be ascertained in this study. In conclusion, the results of this study provide evidence for significant antimicrobial resistance among bacterial isolates from birds. Long term prospective studies involving isolation, identification and antibiogram from more samples are required to identify novel pathogens causing respiratory disease in birds. Such studies provide data on temporal and spatial difference in antibiotic resistance patterns, which in turn helps the scientific community to design better disease control strategies.